Pengaruh Bimbingan Kelompok Untuk Meningkatkan Keterampilan Komunikasi Interpersonal Siswa Di Man Binjai - Muhammad Irwansyah (Proceedings of Annual Conference on Islamic Educational Management, 2021)
This study aims to determine the effect of group guidance to improve students’ interpersonal communication skills. The research method used is Quasi experimental design nonequivalent control group design. The experimental group received treatment in the form of 6 group counseling sessions held twice a week. The control group did not receive treatment. The population in this study was the X grade students of MAN Binjai Science Department in the year 2018. The sampling technique used was non-probability sampling in the form of purposive sampling. The male students who were sampled in this study were 10 people with interpersonal communication skill scores in the low category. The instrument used in determining the sample of this study was an instrument of interpersonal communication skills with four choices in the Likert scale model consisting of 42 valid items with reliability using Cronbach’s alpha of 0.813. Statistical data analysis techniques were performed using descriptive statistics using empirical means to see the average pretest and posttest scores in the experimental and control groups. Hypothesis testing results indicate that the Asymp value. Sig of 0.000, which means through the results of these calculations it can be concluded that the interpersonal communication skills of male students sig <0.05, It means that the increase in interpersonal communication skills of class X MAN Binjai Department of Science treatment group is higher than the control group. The implication of the results of the study is to help improve interpersonal communication skills of class X students at MAN Binjai Science Department